2016
DOI: 10.15446/dyna.v83n196.54189
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on hydrated cement for its reuse in geopolymers

Abstract: <p>The carbonation of hydrated ordinary Portland cement (OPC) allows the transformation of hydrated calcium aluminates and silicates into calcium carbonate and amorphous silica/ alumina. These carbonated materials are appropriate to being used as inorganic precursors for alkaline activation. The use of sodium silicate and hydroxide solutions enables the production of cementitious gels. Two ways of carbonation of hydrated cement were studied: in a dry environment, where relative humidity did not exceed 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, according to the thermogravimetric analysis shown in Table 5, there is a first degradation corresponding to the water occluded within the crystalline network, which was visualized in the infrared spectrum of Figure 1 in the 3410 cm -1 band. On the other hand, it has been reported that the degradations between 600-750°C correspond to the dehydroxylation of Ca (OH) 2 , while at 750-850°C they are due to the decomposition of carbonates into CaO and CO 2 , this due to the amount of calcium contained in the sludge in the form of calcite (Rodríguez et al, 2012;Segura Sierpes et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the thermogravimetric analysis shown in Table 5, there is a first degradation corresponding to the water occluded within the crystalline network, which was visualized in the infrared spectrum of Figure 1 in the 3410 cm -1 band. On the other hand, it has been reported that the degradations between 600-750°C correspond to the dehydroxylation of Ca (OH) 2 , while at 750-850°C they are due to the decomposition of carbonates into CaO and CO 2 , this due to the amount of calcium contained in the sludge in the form of calcite (Rodríguez et al, 2012;Segura Sierpes et al, 2016).…”
Section: Resultsmentioning
confidence: 99%